2003
DOI: 10.1128/jvi.77.22.12336-12345.2003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Functional Analysis of Full-Length Human Immunodeficiency Virus Type 1 env Genes Derived from Brain and Blood of Patients with AIDS

Abstract: The genetic evolution of human immunodeficiency virus type 1 (HIV-1) in the brain is distinct from that in lymphoid tissues, indicating tissue-specific compartmentalization of the virus. Few primary HIV-1 envelope glycoproteins (Envs) from uncultured brain tissues have been biologically well characterized. In this study, we analyzed 37 full-length env genes from uncultured brain biopsy and blood samples from four patients with AIDS. Phylogenetic analysis of intrapatient sequence sets showed distinct clustering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
138
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(145 citation statements)
references
References 49 publications
6
138
1
Order By: Relevance
“…Although it has been demonstrated that HIV-1 envelope sequences in CNS are most closely related to sequences in peripheral blood and bone marrow, 38 it is possible that some MPs are infected as they enter the CNS. Furthermore, there is C, F, and I).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been demonstrated that HIV-1 envelope sequences in CNS are most closely related to sequences in peripheral blood and bone marrow, 38 it is possible that some MPs are infected as they enter the CNS. Furthermore, there is C, F, and I).…”
Section: Discussionmentioning
confidence: 99%
“…39 The relationship between the blood compartment and the CNS is further demonstrated by biological comparison with respect to the frequency of co-receptor utilization specificities. 38 It is possible that some of the differences that have been observed in comparison of brain sequence with other organs 40 may reflect differences in cell populations infected by HIV-1 in particular tissues (ie, the abundance of T cells in lymphoid tissue, but not brain) or, alternatively, mechanisms of immune selection as has been inferred from differences in T-cell epitopes in viruses isolated from different organs. 41 Further studies will be needed combining viral-genetic characterization with immunohistochemical analysis to characterize virus within individual cell populations in multiple organs.…”
Section: Discussionmentioning
confidence: 99%
“…Virtually all strains of HIV-1 interact with cells through the use of either CXCR4 or CCR5 receptors. Many viruses that replicate in the brain use CCR5 (i.e., are M-tropic), although it is now believed that CXCR4 (T-tropic) utilizing or dual specific viral strains may also occur (Ohagen et al, 2003). It is still unclear which viral tropism is more likely to produce brain disease.…”
Section: Hiv-1 and Neurogenesismentioning
confidence: 99%
“…Viruses BL01 and BR07 were provided by Dana Gabuzda of the Dana-Farber Cancer Institute. Both are chimeric infectious molecular clones of NL4-3 that contain the full-length env genes from primary HIV-1 isolates (20). After initial plasmid transfection of 293 cells, these viruses were expanded in PBMC as described above.…”
Section: Methodsmentioning
confidence: 99%